Wildlife conservation and animal temperament: causes and consequences of evolutionary change for captive, reintroduced, and wild populations - McDougall, P.T; Réale, D; Sol, D; Reader, S.M (Animal conservation, 2006)
We argue that animal temperament is an important concept for wildlife conservation science and review causes and consequences of evolutionary changes in temperament traits that may occur in captive-breeding programmes. An evolutionary perspective is valid because temperament traits are heritable, linked to fitness and potentially subject to intense selection in captivity. Natural, sexual and artificial selection can cause permanent shifts in temperament, reducing the diversity of temperament traits, diversity that may be critical to reintroduction success. Breeding programmes that ignore temperament risk leading the captive population towards domestication. Furthermore, shifts in temperament may involve alterations in linked morphological and physiological traits, and selection may even change functional relationships between traits. Captive-breeding programmes can reduce changes in temperaments by closely monitoring temperament traits, equalizing reproductive success between temperament morphs and using environmental enrichment to reduce captive stress. Under certain circumstances, knowledge about temperament may also provide a useful tool to optimize captive reproduction and to increase reintroduction success. Outside reintroduction programmes, temperament can mediate responses to human contact, hunting, exploitation, habitat fragmentation and disease transmission. Consideration of temperaments could strengthen both captive and wild conservation efforts.